Jaffe-Campanacci syndrome presenting as young stroke - Manivannan, Prince Rueban; S., Sakthi Kumar; P., Abishekapriyan (International Journal of Research in Medical Sciences, 2026)
Jaffe-Campanacci syndrome is a rare clinical entity characterized by multiple non-ossifying fibromas, café-au-lait macules, and various extraskeletal manifestations, which have a debated association with neurofibromatosis type 1. Fewer than 30 cases have been reported in the literature, making the diagnosis and characterization of this disease challenging. We report a rare case of a 16-year-old girl who presented with an acute onset of headache, left-sided weakness, slurring of speech, and sudden loss of consciousness. Neuroimaging revealed a right gangliocapsular haemorrhage with a midline shift, consistent with a haemorrhagic stroke. MRI confirmed a large subacute intracerebral haemorrhage, and genetic analysis revealed positivity for the NF1 gene mutation. This case is noteworthy because haemorrhagic stroke is an extremely uncommon presentation of Jaffe-Campanacci syndrome and highlights the possible association between vascular abnormalities and the syndrome. Early identification of the characteristic skeletal and cutaneous manifestations is essential for the correct diagnosis and correct medical management. Reporting such unusual presentations of Jaffe Campanacci syndrome contributes to a better understanding of the disease spectrum and its relationship with neurofibromatosis type 1.